An evidence-based forensic taxonomy of windows phone dating apps - Wahyu Cahyani, Niken Dwi; Kim-Kwang, Raymond Choo; Ab Rahman, Nurul Hidayah; Ashman, Helen (John Wiley & Sons, Inc., 2019)
Advances in technologies including development of smartphone features have contributed to the growth of mobile applications, including dating apps. However, online dating services can be misused. To support law enforcement investigations, a forensic taxonomy that provides a systematic classification of forensic artifacts from Windows Phone 8 (WP8) dating apps is presented in this study. The taxonomy has three categories, namely: Apps Categories, Artifacts Categories, and Data Partition Categories. This taxonomy is built based on the findings from a case study of 28 mobile dating apps, using mobile forensic tools. The dating app taxonomy can be used to inform future studies of dating and related apps, such as those from Android and iOS platforms.